2004
DOI: 10.1074/jbc.m313004200
|View full text |Cite
|
Sign up to set email alerts
|

The Low Density Lipoprotein Receptor-related Protein Is a Motogenic Receptor for Plasminogen Activator Inhibitor-1

Abstract: Although plasminogen activator inhibitor-1 (PAI-1) is known to stimulate cell migration, little is known about underlying mechanisms. We show that both active and inactive (e.g. cleaved) PAI-1 can activate the Jak/Stat signaling system and stimulate cell migration in chemotaxis, haptotaxis, chemokinesis, and wound healing assays. Moreover, antibodies to the LDL receptor-related protein (LRP) and an LRP antagonist (RAP) blocked these motogenic effects of PAI-1, while a PAI-1 mutant that did not bind to LRP fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
206
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(215 citation statements)
references
References 57 publications
6
206
3
Order By: Relevance
“…Because apoptotic cell clearance is critical to the resolution of inflammation, our data suggest that PAI-1 may exacerbate inflammatory responses by blocking the clearance of apoptotic neutrophils, thereby allowing such neutrophils to become necrotic and to release their intracellular contents into the extracellular milieu. Our findings, together with previous studies demonstrating that PAI-1 enhances LPS induced neutrophil activation (22) and promotes the migration and infiltration of lymphocytes and neutrophils into inflammatory sites (19)(20)(21)27), demonstrate that PAI-1 has multiple proinflammatory roles that are independent of its participation in coagulation and microvascular thrombosis. We found that the enhanced neutrophil phagocytosis associated with PAI-1 deficiency can be abrogated by blocking LRP on macrophages with anti-LRP antibodies or the LRP-specific blocking peptide RAP, indicating that LRP participates in PAI-1 mediated modulation of efferocytosis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Because apoptotic cell clearance is critical to the resolution of inflammation, our data suggest that PAI-1 may exacerbate inflammatory responses by blocking the clearance of apoptotic neutrophils, thereby allowing such neutrophils to become necrotic and to release their intracellular contents into the extracellular milieu. Our findings, together with previous studies demonstrating that PAI-1 enhances LPS induced neutrophil activation (22) and promotes the migration and infiltration of lymphocytes and neutrophils into inflammatory sites (19)(20)(21)27), demonstrate that PAI-1 has multiple proinflammatory roles that are independent of its participation in coagulation and microvascular thrombosis. We found that the enhanced neutrophil phagocytosis associated with PAI-1 deficiency can be abrogated by blocking LRP on macrophages with anti-LRP antibodies or the LRP-specific blocking peptide RAP, indicating that LRP participates in PAI-1 mediated modulation of efferocytosis.…”
Section: Discussionmentioning
confidence: 78%
“…Elevated serum and tissue levels of PAI-1 have been found in a number of inflammatory diseases, including myocardial infarction, sepsis, and acute lung injury, with increased circulating PAI-1 levels being associated with unfavorable outcomes (15)(16)(17)(18). Previous studies suggested that microvascular thrombosis associated with inhibition of fibrinolytic processes by PAI-1 and the role of PAI-1 as a chemotactic factor promoting the migration of lymphocytes and neutrophils into inflammatory sites contributed to its inflammatory effects (19)(20)(21). In addition, PAI-1 also appears to have intrinsic proinflammatory properties by potentiating Toll-like receptor 4 (TLR4) mediated activation of neutrophils (22).…”
mentioning
confidence: 99%
“…Given this, it was unnecessary to investigate the impact of uPA-SerpinB2 KYK (or other SerpinB2 mutants generated with incomplete LDLR-binding motifs) on mitogenic signaling, because the VLDLR binding affinity of this complex was indistinguishable from that of uPASerpinB2 YK . Direct binding of SerpinE1 to LRP1 has also been demonstrated to activate the JAK/STAT pathway, leading to increased cell motility (34). However, because the prognostic data for SerpinE1 is only significant in tumors also expressing uPA (1)(2)(3)35), the impact of complementing SerpinB2 with LRP1 binding on the activation of this pathway was not investigated in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Although both are efficient uPA inhibitors, PAI-1 and PAI-2 are structurally and functionally quite distinct serpins, as recognized by their grouping into different serpin subfamily groups (6). For example, PAI-1 also has alternative non-uPA inhibitory activities that affect cell adhesion, intracellular signaling, and cell migration (8) that have not been demonstrated for PAI-2.…”
mentioning
confidence: 99%